A rare case of bilateral high origin of the testicular artery with variations in the course and branches. - Prasanna LC; Babu A; D’Souza AS; Bhat KMR (Department of Surgery, UKM Medical Centre, 2014)
In general, testicular artery (TA) usually arises from the antero-lateral part of the abdominal aorta below the origin of the renal arteries at second lumbar vertebrae level. Very rarely variations in the origin of the testicular arteries are observed. We here report a rare case of bilateral unusual origin and course of the testicular artery. On the right side, testicular artery aroused from the aorta about 0.5cm above the origin of the renal artery and gave off inferior suprarenal artery. In contrast, left testicular artery springs from the pre-hilar branch of the left renal artery, 2cm before reaching the hilum of kidney. On both sides, testicular arteries descended in front of the hilar structures of the kidney. Since, the origin and course of the testicular artery is important to consider during surgical and diagnostic interventions, knowledge of such variation may be helpful in avoiding diagnostic and surgical errors and adverse consequences especially during laparoscopic approaches.